The excavation disturbed zone (EDZ) at Kiirunavaara mine, Sweden—by seismic measurements - Malmgren, L.; Saiang, D.; Töyrä, J.; Bodare, A. (Journal of applied geophysics, 2007)
The presence of an excavation disturbed zone (EDZ) around an excavation boundary can significantly affect the overall performance of the excavation and the general safety of men and equipment. Hence, it has been an important subject of research in various rock excavation projects. The EDZ is generally defined as the rock zone beyond the excavation boundary where the physical, mechanical and hydraulic properties of the rock have been significantly affected due to the excavation and redistribution of stresses. For LKAB's Kiirunavaara underground iron ore mine in Sweden, the understanding of the EDZ is essential for optimal design of rock support. With this main objective an EDZ investigation was conducted at the mine using seismic measurement techniques. Cross-hole seismics and spectral analyses of surfaces waves (SASW) were the main techniques used. Borehole Image Processing Systems (BIPS) complemented the seismic measurements. The results show that an EDZ with a thickness of 0.5–1. 0 m existed behind the boundaries of the mining drifts being investigated. The magnitude of the Young's modulus of this zone was 50% to 90% of that of the undisturbed rock.